Assessing heavy metal contamination and soil fertility in degraded farmland adjacent to nickel mining: Pathway towards sustainable land management in Halmahera Region, Indonesia - Ishak, Lily; Teapon, Amiruddin; Subur, Riyadi; Armaijn, Liasari; Sidayat, Mardiyani; Abdul Rachman, Idris; Ladjinga, Erwin (Brawijaya University, 2026)
A continuous decline in crop yields in the Halmahera region of Indonesia, has been attributed to potential soil contamination by heavy metals from mining activities. Yet, the extent to which such contamination directly drives farmland degradation in this region remains undercover. This study aims to quantify the concentration and spatial distribution of selected heavy metals, evaluate their ecological risks, assess soil fertility in the affected areas, and propose directions on future research for sustainable land management (SLM). Sixteen soil samples were collected and analyzed for physicochemical properties and concentrations of Fe, Ni, As, Cd, Co, and Hg. The results indicates that Fe exhibited the highest concentration (11,894 mg kg?¹), whereas Hg was negligible. Strong positive correlations and similar spatial distribution patterns were observed among Fe, Ni, and Co, which distincted from those of As and Cd. The pollution load index revealed moderate contamination for Fe and low contamination for other metals, while geoaccumulation index values ranged from low to moderate, reflecting contributions from both natural and anthropogenic sources. Ecological risk assessment indicated a low risk level. Additionally, soil fertility was considered low, characterized by reduced organic carbon, nitrogen, potassium, cation exchange capacity, and base saturation. Findings of this study provide a crucial foundation for future research to develop a conceptual framework for SLM that supports farmland restoration, improves soil health, increases crop yields and ecosystem services, and enhances the knowledge and economic benefits of local communities in this region.